Segregated Co-activation Patterns in the Emergence of Decision Confidence During Visual Perception - Jaeger, Cilia; Glim, Sarah; Dimulescu, Cristiana; Ries, Anja; Sorg, Christian; Wohlschläger, Afra (Frontiers in Systems Neuroscience, 2020)
Visual metacognition - the introspection and evaluation of one’s own visual perceptual processes - is measured through both decision confidence and ‘metacognitive efficiency’. Metacognitive efficiency refers to an individual’s ability to accurately judge incorrect and correct decisions through confidence ratings given their task performance. Previous imaging studies in humans and nonhuman primates reported widely distributed brain regions being involved in decision confidence and metacognition. However, the neural correlates of metacognition are remarkably inconsistent across studies with respect to spatial outline. Therefore, this study investigates neural correlates of visual metacognition by examining co-activation across regions that scale with visual decision confidence. We expected that co-activation across regions varying relative to decision confidence might give insight into how metacognition arises in the brain. To test this hypothesis, we performed task-fMRI in healthy humans during a visual backward masking task with four-scale, post-decision confidence ratings. We measured blood oxygenation covariation patterns, which served as a physiological proxy for co-activation across brain regions. Decision confidence ratings and individual’s metacognitive efficiency served as behavioral measures for metacognition. We found three distinct co-activation clusters involved in decision confidence: the first included right-centered fronto-temporal-parietal regions, the second included left temporal and parietal regions and the left basal forebrain, and the third included cerebellar regions. The right fronto-temporal-parietal cluster including the supplementary eye field and the right basal forebrain showed stronger co-activation in subjects with higher metacognitive efficiency. Our results provide novel evidence for co-activation of widely distributed fronto-parieto-temporal regions involved in visual confidence. The supplementary eye field was the only region that activated for both decision confidence and metacognitive efficiency, suggesting the supplementary eye field plays a key role in visual metacognition. Our results link findings in electrophysiology studies and human fMRI studies and provide evidence that confidence estimates arise from the integration of multiple information processing pathways.